Morphological aspects of atrioventricular valves in the ostrich (Struthio camelus) - Marcelo Abidu-Figueiredo; Clarice Machado Santos; Marco Aurélio Pereira Sampaio; Maurício Alves Chagas (Biotemas)
Heart anatomy in the ostrich has been reported, but there are few information on the histological features of the atrioventricular valves. Hearts of young ostriches were fixed in 10% formaldehyde for 24 h and dissected to characterize their macroscopic anatomy. Samples of valves were harvested and stained with Mallory’s trichrome, Gomori’s trichrome, and Picro-Sirius red, for later analysis. The right atrioventricular valve consists of a muscle flap with two fixations. The left atrioventricular valve consists of two layers of endocardium with a layer of connective tissue between them. The free border of the tricuspid valve supports a varying number of chordae tendineae. One of the cusps is attached to the septum, while the other two cusps are attached to the opposite wall. The aortic valve, as well as the pulmonary trunk valve, consists of three cusps. The right atrioventricular valve showed up only as a muscle flap of myocardium coated with a thin layer of dense connective tissue, with two fixations. In the connective tissue, we find a predominance of type I collagen fibers and a lesser amount of type III, with a small presence of elastic fibers. The presence of Purkinje fibers were also usual in the valvular subendocardium, suggesting that they directly participate in the transmission of nervous stimulation to the muscle fibers within the valves. The left atrioventricular valve consisted of 3 cusps, a dorsal, a left, and a right.